Intensity-Dependent Changes in Quantified Resting Cerebral Perfusion With Multiple Sessions of Transcranial DC Stimulation - Sherwood, Matthew S.; McIntire, Lindsey; Madaris, Aaron T.; Kim, Kamin; Ranganath, Charan; McKinley, R. Andy (Frontiers in Human Neuroscience, 2021)
Transcranial direct current stimulation (tDCS) to the left prefrontal cortex has been shown to produce broad cognitive effects including enhanced learning and vigilance. Still, the neural mechanisms underlying such effects are not fully understood. Furthermore, the neural underpinnings of repeated stimulation remain undetermined. In this work, we evaluated the effects of repetition and intensity of tDCS on cerebral perfusion. 1 or 2mA tDCS was applied to the left prefrontal cortex on three consecutive days and resting cerebral perfusion was quantified before and after stimulation using arterial spin labeling MRI, then compared with a group which received sham stimulation. Widespread decreased perfusion was found in a group receiving sham stimulation across the 3 post-stimulation measures when compared with baseline; increasing in magnitude, extent and significance across the study. Slight decreases were observed in the group receiving 2mA stimulation in the second and third post-stimulation measurement, but more prominent increased perfusion was observed as well. Interestingly, the 1mA group appeared similar to the sham group across the first two post-stimulation measures with increasing, widespread lower perfusion. However, these decreases were mitigated in the third post-stimulation scan with even increased perfusion observed in some brain areas similar to the 2mA group. Our findings indicate that the neural effects of stimulation may persist for at least 24hrs and that repeated stimulation may produce summative effects.